Adapting a novel emergency triage tool to a resource-limited hospital in Nepal - Yael Weiner; Claire Therriault; Tina Duwal; Samjhana Basnet; Roshana Shrestha; Sanu Krishna Shrestha (International Journal of Emergency Medicine)
Abstract Background Effective triage is critical for prioritizing emergency care. However, many low- and middle-income countries lack standardized triage systems. Nepal has been working to introduce the WHO’s Interagency Integrated Triage Tool (IITT) into emergency departments nationwide. Still, successful implementation requires context-specific adaptations to address operational realities and resource constraints. Objective This study aimed to collaboratively adapt the IITT for use in the Dhulikhel Hospital Emergency Department by incorporating frontline staff insights to develop a feasible, sustainable triage workflow. Methods Five focus groups composed of doctors, nurses, and paramedics were conducted. Through semi-structured discussions, we explored staff perceptions of areas for improvement in the existing triage processes. Participants then generated site-specific workflow models through iterative brainstorming sessions, progressively refining the design into a final consensus-based model. Results Participants, representing over 80% of clinical staff, identified key barriers to effective triage, including inconsistent communication, unclear handoff responsibilities, and insufficient training. The final triage workflow addressed many critical challenges raised in discussion sessions, provided a standardized and customized triage process, and resulted in high reported confidence in its utility. Conclusion This study demonstrates the value of a bottom-up, staff-centered approach to triage system development and implementation. Our focus group design offers a practical, replicable framework for low-resource emergency departments seeking to implement the IITT or similar protocols into their ED operations. Future efforts should focus on validating the workflow’s impact on patient outcomes and triage efficiency and investing in thorough and longitudinal training to support sustained adoption.